Gelatin-based biomaterials as a delivery strategy for osteosarcoma treatment - Yang, Qifan; Chen, Xingpeng; Liu, Jing; He, Yeteng (Frontiers in Pharmacology, 2025)
Osteosarcoma is the most common primary malignant bone tumor. Although surgery and chemoradiotherapy have made some progress in the treatment of osteosarcoma. However, the high recurrence and metastasis rate of osteosarcoma and bone defects caused by surgery are still the main problems faced by osteosarcoma. Gelatin has excellent biocompatibility and biodegradability, and has made phased progress in tumor treatment. In the treatment of osteosarcoma, gelatin-based biomaterials can be used in delivery strategies to enhance the anti-tumor activity of osteosarcoma and can improve the appropriate compressive strength to improve the bone defects faced after surgery. At present, gelatin-based hydrogels, gelatin scaffolds, and gelatin-based nanoparticles have been reported in preclinical studies. In this article, we introduce the application of gelatin-based biomaterials in the treatment of osteosarcoma, and summarize and look forward to them.